Impact of Information Technology and E-business Amongst Indian Micro & Small to Medium Sized Enterprises (MSME) Wholesalers for Supply Chain Management - Rajendran, Lajesh Kolath (2012)
The aim of the research was to investigate the impact of information technology and its application amongst micro & small to medium sized enterprises (MSME) wholesalers for supply chain management (SCM). The extent to which information technology and its applications are practiced and attitudes towards e-business were investigated. A qualitative research approach was chosen for this study. The method of qualitative interviewing through the administration of semi-structured interviews was used to capture rich and in-depth data. The research showed that nine of the ten MSMEs interviewed, already use information technologies and its applications for their businesses. Effective use of Information technology and its applications are important aspects of a successful business and the majority of MSME owners interviewed agreed to this. The contributions of this research lie in the implications for wholesale MSMEs in India from the useful insights of their peers in the industry; to the government in development of initiatives and assistance for the important MSME sector; and in expanding the use of IT, e-business and SCM as well as creating grounds for further research.